Is Foreign Exchange Market Intervention an Alternative to Monetary Policy? Evidence from Japan - Rasmus Fatum; Michael M. Hutchison (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
Japanese official intervention in the foreign exchange market is of by far the largest magnitude in the world, despite little or no evidence that it is effective in moving exchange rates. Up until recently, however, official data on intervention has not been available for Japan. This paper investigates the effectiveness of intervention using recently published official daily data and an exchange rate data, i.e. intense and sporadic bursts of intervention activity juxtaposed against a yen/dollar rate continuously changing, than standard time-series approaches. Focusing on daily Japanese and US official intervention operations, we identify separate intervention episodes and analyze the subsequent effect on the exchange rate. Using the non-parametric sign test and matched-sample test, we find strong evidence that sterilized intervention systematically affects the exchange rate in the short-run. This result holds even when intervention is not associated with (simultaneous) interest rate changes and regardless of whether or not intervention is secret (in the sense of no official reports or rumors of intervention reported over the newswires). To some extent intervention might be a useful policy instrument during the zero-interest rate policy period in Japan, effectively depreciating the value of the yen exchange rate (the foolproof policy proposed by Svensson, 2001), but the effects are likely to be short-term in nature.
Keywords: 330; Wechselkurspolitik; Geldpolitik; Vergleich; Japan